Sourdough powder: physicochemical, microbiological properties and shelf-life stability in different package type - Hajar-Azhari, Siti; Mohd Roby, Bizura Hasida; Jemain, Siti Noorafiqah; Meor Hussin, Anis Shobirin (Springer, 2024)
This study aims to optimize the culture condition of semi-liquid sourdough using Kombucha as a starter culture and to evaluate the physicochemical properties, microbial viability and recovering ability of sourdough powder when packaged in different types of packaging for 120 days. Optimal maturation time (103.47 h) and maximum leavening rate (1.27 mL/h) of sourdough were achieved at an incubation temperature of 34 °C and interval refreshment time at 7 h. The optimized culture was spray-dried using 3% Arabic gum (w/v) as a carrier agent yielding 35.86% powder with acceptable viability of 8.71 log CFU/g lactic acid bacteria and 9.03 CFU/g yeast. The sourdough powder was packed in four packaging (LDPE, vacuumed LDPE, aluminum foil laminated pouch and vacuumed aluminum foil laminated pouch) and exhibited comparable physicochemical properties during 120 days of storage. The viability of both lactic acid bacteria and yeast count in sourdough powder when packed in vacuumed aluminum foil laminated pouch showed higher stability for 90 days (6.18 log CFU/g and 6.82 log CFU/g) but reduced to below detection limit after 120 days (5.54 and 5.94 log CFU/g). This suggested that Kombucha sourdough powder packed in vacuumed aluminum laminated pouch could be stored for up to 90 days. © Association of Food Scientists & Technologists (India) 2024.